2021
DOI: 10.18097/pbmc20216703244
|View full text |Cite
|
Sign up to set email alerts
|

Peptide inhibitors of the interaction of the SARS-CoV-2 receptor-binding domain with the ACE2 cell receptor

Abstract: Computer simulation has been used to identify peptides that mimic the natural target of the SARS-CoV-2 coronavirus spike (S) protein, the angiotensin converting enzyme type 2 (ACE2) cell receptor. Based on the structure of the complex of the protein S receptor-binding domain (RBD) and ACE2, the design of chimeric molecules consisting of two 22-23-mer peptides linked to each other by disulfide bonds was carried out. The chimeric molecule X1 was a disulfide dimer, in which edge cysteine residues in the precu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…In a number of other laboratories, almost at the same time, the same hypothesis about the possibility of blocking the entry of the SARS-CoV-2 virus into the cell using a peptide analog of the ACE2 region, crucial for the interaction with RBD, was tested using various synthetic peptides [ 24 26 ]. R. Larue et al [ 27 ] found that very short peptides (only 6‒16 a.a.) containing a portion of the α1 helix and belonging to self-assembling peptides (SAPs) inhibited binding of S-protein-containing PVPs to ACE2, although at least one of these peptides did not bind to the S protein in vitro at all.…”
Section: Resultsmentioning
confidence: 99%
“…In a number of other laboratories, almost at the same time, the same hypothesis about the possibility of blocking the entry of the SARS-CoV-2 virus into the cell using a peptide analog of the ACE2 region, crucial for the interaction with RBD, was tested using various synthetic peptides [ 24 26 ]. R. Larue et al [ 27 ] found that very short peptides (only 6‒16 a.a.) containing a portion of the α1 helix and belonging to self-assembling peptides (SAPs) inhibited binding of S-protein-containing PVPs to ACE2, although at least one of these peptides did not bind to the S protein in vitro at all.…”
Section: Resultsmentioning
confidence: 99%